Sufi-Healing sebagai Model Terapi Penyakit Hati: Analisa Pemikiran Ibn Qayyim Al-Jauziyah - Arroisi, Jarman; Al Faruqi, Achmad Reza Hutama; Basith, Muhammad (Program Studi Tasawuf dan Psikoterapi, 2024)
This article examines the model of heart disease therapy in the thought of Ibn Qayyim Al-Jauziyah, known as Sufi healing. It aims to purify the heart from disease while enabling a servant to fulfill their worship as commanded by Allah to His Messenger. In life, a person inevitably encounters four conditions: pleasure, sorrow, suffering, and death. This study investigates how Sufi healing impacts the ability to face these four conditions. The author employs descriptive and analytical methods in this research. After conducting a literature review, the author concludes that Sufi healing, according to Ibn Qayyim's thought, is an effective way to treat heart diseases by engaging in remembrance (dhikr) of Allah. This practice leads to human happiness and protection from diseases such as envy, jealousy, malice, and ostentation.